2015
DOI: 10.1155/2015/785474
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Perfusion-Decellularization Methods of Porcine Livers for Clinical-Scale Whole-Organ Bioengineering

Abstract: Aim. To refine the decellularization protocol of whole porcine liver, which holds great promise for liver tissue engineering. Methods. Three decellularization methods for porcine livers (1% sodium dodecyl sulfate (SDS), 1% Triton X-100 + 1% sodium dodecyl sulfate, and 1% sodium deoxycholate + 1% sodium dodecyl sulfate) were studied. The obtained liver scaffolds were processed for histology, residual cellular content analysis, and extracellular matrix (ECM) components evaluation to investigate decellularization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 34 publications
1
69
0
Order By: Relevance
“…Tchen et al [2007] reported that detergents like SDS/ Triton X-100 would disrupt the ECM ultrastructure in pancreatic bioscaffold with a high fat content. SDS tends to destroy the native tissue ultrastructure and can destabilize the triple-helical domain and integrity of collagen [Wu et al, 2015b]. In this study, a colorimetric assay was used to detect hydroxyproline, a major element of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Tchen et al [2007] reported that detergents like SDS/ Triton X-100 would disrupt the ECM ultrastructure in pancreatic bioscaffold with a high fat content. SDS tends to destroy the native tissue ultrastructure and can destabilize the triple-helical domain and integrity of collagen [Wu et al, 2015b]. In this study, a colorimetric assay was used to detect hydroxyproline, a major element of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that triton x‐100 is not as effective as sodium dodecyl sulfate (SDS) for DNA removal, it better preserves the matrix architecture and endogenous growth factors, which play important roles in modulating cellular functions . Studies have also demonstrated that triton‐x100 treated decellularized liver scaffolds supported superior hepatic cell functions when compared to SDS treated counterparts . Triton x‐100 has also been used for preparing liver scaffolds of a clinical relevant scale …”
Section: Discussionmentioning
confidence: 99%
“…Primary rat hepatocytes were isolated from male Sprague-Dawley rats (body weight, 180–220 g) by a two-step collagenase perfusion method, and their viability was confirmed to be >95% by the trypan blue exclusion method (12). Hepatocytes were cultured in serum-free medium as previously described (13).…”
Section: Methodsmentioning
confidence: 99%